Exploring Challenges in the English as a Foreign Language Learning Process in Primary Schools Arising from Cultural Diversity - Nasution, Ismail Saleh; Kharisma, Adib Jasni; Ginting, Pirman (Universitas PGRI Sumatera Barat, 2024)
This study examines the perspectives and experiences of the researcher, elementary school English educators, students, and parents with regard to the challenges associated with learning English as a foreign language, particularly in the context of cultural factors. It also investigates potential strategies to incorporate cultural elements into the English learning process to enhance its efficacy. This research adopts a multi-paradigm transformative approach, employing methodologies such as Critical Autoethnography, Inquiry through Writing, postmodern interview-based interviews, and document and literature review. The findings of this study reveal that both the researcher and teachers acknowledge a significant relationship between culture and the process of learning English, suggesting that integrating aspects of diverse cultures into English language instruction holds promise as a novel approach to facilitate English language acquisition within elementary school settings.